Pengaruh Narasi Visual Trailer Game Grand Theft Auto VI terhadap Minat Beli (Survei pada Komunitas GTA V Roleplay Indonesia di Facebook) - Satria Airlangga Setiawan; Velda Ardia (Dialogika : Jurnal Penelitian Komunikasi dan Sosialisasi, 2026)
The game industry in Indonesia has shown significant growth in recent years, along with the increasing public interest in high-quality video games. AAA (triple-A) games such as Grand Theft Auto VI (GTA VI) rely heavily on trailers as their primary promotional tool to introduce the game’s atmosphere, visual quality, and complex storytelling. GTA is widely recognized as a pioneer in realistic visuals, deep narratives, and social criticism delivered through iconic storytelling, making it highly appealing to potential consumers. This study aims to examine the influence of visual narrative in the GTA VI trailer on consumers’ purchase intention within the Indonesian GTA V Roleplay Facebook community. The theoretical framework is based on Marketing Communication Theory, Visual Narrative Theory with the dimensions of clarity, realism, dynamism, and continuity, as well as Purchase Intention Theory consisting of transactional, referential, preferential, and exploratory intentions. A quantitative approach was employed using a survey method, with questionnaires as the data collection instrument. The sample was selected using simple random sampling and calculated using the Slovin formula with a 5% margin of error, resulting in 92 respondents. The results indicate that the visual narrative variable achieved the highest mean score in the realism dimension (3.29), while purchase intention recorded the highest mean score in the transactional intention dimension (3.79). Simple linear regression analysis reveals that visual narrative has a significant influence on purchase intention, with a correlation coefficient (R) of 0.918. The coefficient of determination (R²) of 0.843 indicates that 84.3% of purchase intention is influenced by visual narrative, while the remaining 15.7% is affected by other factors beyond this study.